Hubungan Persepsi Perawat Tentang Karakteristik Pekerjaan Dengan Kepatuhan Dalam Pendokumentasian Asuhan Keperawatan - Ageng Abdi Putra; Sri Rejeki; Tri Nur Kristina (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2016)
Background: Nursing documentation is very important, however the implementation is often ignored especially in the aspect of completeness, accuracy, and quality of documentation. Work characteristics is the identification of the various dimensions of work such as the nature and types of tasks, professional behaviors and attitudes to achieve optimal performance. Method: Observational study with cross sectional approach. Samples were 62 nurses in the inpatient department indistricht hospitals in Mataram. Result: Perception of nurses on their job characteristics were good (72.6% ) , whereas the adherence in nursing documentation were also categorized as good (90.3 %). Statistical test correlation using pearson product moment showedweak and significant association (r = 0.306; p = 0.016). Skill variety, taks identity and significance have association with compliance, while otonomy and feedback have not related to compliance. Conclusion: There is a relationship between nurse's perceptions of their job characteristics with compliance in nursing documentation. of nursing care. The management need to adjust the characteristics of nursing characteristic including reward and warning.